PSYCHOLINGUISTICS AND COGNITIVE SCIENCE IN SIMULTANEOUS INTERPRETATION (International Conference on Modern Science and Scientific Studies, 2025)
In recent years, the issue of simultaneous interpretation has become increasingly important due to simultaneous interpreters rely heavily on working memory to hold and process information from the source language while formulating an equivalent in the target language. Cognitive science studies how interpreters manage this dual task, often switching between listening and speaking almost simultaneously. The interpreter’s brain must balance the cognitive load, managing incoming information, language production, and sometimes cultural adaptation, all while avoiding overload. Research in cognitive science helps to understand the limits of this processing capacity and how interpreters can optimize their mental resources. Interpreters often switch between languages quickly, a process that involves complex cognitive mechanisms. Psycholinguistics explores how bilingual individuals manage this switching, how they keep both languages active in their minds, and how they suppress interference from the non-target language. Cognitive science studies how interpreters inhibit the non-active language and avoid code-switching errors, ensuring that they stay within the confines of the target language while translating.